PEMANFAATAN JERAMI PADI SEBAGAI PUPUK ORGANIK MELALUI PEMBERDAYAAN KELOMPOK TANI DI DESA BONTOLEBANG KABUPATEN TAKALAR - Subaedah, St (Jurnal BALIRESO, 2018)
Bontolebang Village North Galesong District Takalar Regency is one of the areasthat became the center of vegetable plant development. The problem facing thevegetable farmer groups is the management of unfriendly farming system.Farmers in managing their farms rely on the use of chemical fertilizers to improvesoil fertility, without considering the long-term effects of using chemicals.Besides that, farmers are not skilled to make organic fertilizer from waste crops(rice straw) previously that many are found around the farms. This activity aims toincrease knowledge and skills for the farmers in Bontolebang Village, especiallySabar Farmer Group in the management of soil fertility for cultivation whichincludes counseling of environmentally friendly farming system, making oforganic fertilizer from existing crop waste (rice straw) and organic fertilizerapplication right method, so the growth and production of vegetables can bemaximized. The methods used in the implementation of the CommunityPartnership Program are counseling, training, production assistance, anddemonstration plots. The result of this program is the increasing of farmerunderstanding about farming system which is friendly in environment, theincreasing of farmers skill in making organic fertilizer from rice straw, andincreasing of farmer consciousness in the use of organic fertilizer in farming field.